2012
DOI: 10.1007/s13361-012-0451-6
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying Protein-Ligand Binding Constants using Electrospray Ionization Mass Spectrometry: A Systematic Binding Affinity Study of a Series of Hydrophobically Modified Trypsin Inhibitors

Abstract: NanoESI-MS is used for determining binding strengths of trypsin in complex with two different series of five congeneric inhibitors, whose binding affinity in solution depends on the size of the P3 substituent. The ligands of the first series contain a 4-amidinobenzylamide as P1 residue, and form a tight complex with trypsin. The inhibitors of the second series have a 2-aminomethyl-5-chloro-benzylamide as P1 group, and represent a model system for weak binders. The five different inhibitors of each group are ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 56 publications
1
45
0
1
Order By: Relevance
“…Many studies have been performed to determine binding constants for various protein–ligand complexes with ESI-MS [4146]. In this study, we use IMS-MS data to calculate K A s for Zn 2+ bound to OT.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been performed to determine binding constants for various protein–ligand complexes with ESI-MS [4146]. In this study, we use IMS-MS data to calculate K A s for Zn 2+ bound to OT.…”
Section: Resultsmentioning
confidence: 99%
“…In this way they quantified the affinities of methylmannose polysaccharides for lipids [65]. Cubrilovic et al have looked at the binding strength of trypsin with different five congeneric inhibitors whose structure differs only in the substituent group and found that nano-ESI-MS could successfully capture the trend in the binding affinity [66]. The effect of DMSO, a common solvent in high-throughput screening studies, on protein-ligand binding equilibrium was also studied [67].…”
Section: Ion Mobility and Measurement Of Collision Cross Sectionsmentioning
confidence: 99%
“…However, back-scattering interferometry (BSI) is a free-solution label-free technique with the added benefit of sensitivity that rivals fluorescence (9). There are other techniques performed in free solution, such as MS (10, 11) and NMR (12,13) and the widely used isothermal titration calorimetry (ITC) (14, 15). As with NMR, ITC has many advantages, but exhibits modest sensitivity and often requires large sample quantities.…”
mentioning
confidence: 99%